Cluster Analysis of Autoantibodies in 852 Patients with Systemic Lupus Erythematosus from a Single Center - Artim-Esen, Bahar; Cene, Erhan; Sahinkaya, Yasemin; Ertan, Semra; Pehlivan, Ozlem; Kamali, Sevil; Gul, Ahmet; Ocal, Lale; Aral, Orhan; Inanc, Murat (J RHEUMATOL PUBL CO, 2014)
Objective. Associations between autoantibodies and clinical features have been described in systemic lupus erythematosus (SLE). Herein, we aimed to define autoantibody clusters and their clinical correlations in a large cohort of patients with SLE. Methods. We analyzed 852 patients with,SLE who attended our clinic. Seven autoantibodies were selected for cluster analysis: anti-DNA, anti-Sm, anti-RNP, anticardiolipin (AT) immunoglobulin (Ig)G or IgNt lupus anticoagulant (LAC), anti-Ro, and anti-La. Two-step clustering and Kaplan-Meier survival analyses were used. Results. Five clusters were identified. A cluster consisted of patients with only anti-dsDNA antibodies, a cluster of anti-Sm and anti-RNP, a cluster of aCL IgG/M and LAC, and a cluster of anti-Ro and anti-La antibodies. Analysis revealed 1 more cluster that consisted of patients who did not belong to any of the clusters formed by antibodies chosen for cluster analysis. Sm/RNP cluster had significantly higher incidence of pulmonary hypertension and Raynaud phenomenon. DsDNA cluster had the highest incidence of renal involvement. In the aCL/LAC cluster, there were significantly more patients with neuropsychiatric involvement, antiphospholipid syndrome, autoimmune hemolytic anemia, and thrombocytopenia. According to the Systemic Lupus International Collaborating Clinics damage index, the highest frequency of damage was in the aCL/LAC cluster. Comparison of 10 and 20 years survival showed reduced survival in the AcL/LAC cluster. Conclusion. This study supports the existence of autoantibody clusters with distinct clinical features in SLE and shows that forming clinical subsets according to autoantibody clusters may he useful in predicting the outcome of the disease. Autoantibody clusters in SLE may exhibit differences according to the clinical setting or population.
Keywords: SYSTEMIC LUPUS ERYTHEMATOSUS; CLUSTER; AUTOANTIBODLES; DISEASE PATTERN; DAMAGE; SURVIVAL; AUTOIMMUNE HEMOLYTIC-ANEMIA; ANTIPHOSPHOLIPID SYNDROME; COGNITIVE FUNCTION; ORGAN DAMAGE; ANTI-SM; ANTIBODIES; DISEASE; MANIFESTATIONS; PATTERNS; FEATURES; Rheumatology